2023
DOI: 10.3390/v15020302
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the LTR Region of Polish SRLVs and Its Impact on the Transcriptional Activity of Viral Promoters

Abstract: A long terminal repeat (LTR) plays an indispensable role in small ruminant lentivirus (SRLV) gene expression. In this study, we present the LTR sequence of Polish SRLVs representing different subtypes, and analyzed their impact on SRLV promoter activity, as measured in transient transfection assays. Although certain nucleotide motifs (AML(vis), TATA box and the polyadenylation site (AATAAA)) were conserved across sequences, numerous mutations within the LTR sequences have been identified. Single nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The relation between SRLV subtypes and their biological features is not clear, although several subtype-specific markers in the LTR of SRLV have been identified by Olech et al (120), who also revealed different levels of promoter activity for strains representing different subtypes. Therefore, differences between subtypes may be responsible for different transcriptional activity and replication rates, which may result in biological differences between SRLV subtypes.…”
Section: Tropism and Pathologymentioning
confidence: 99%
“…The relation between SRLV subtypes and their biological features is not clear, although several subtype-specific markers in the LTR of SRLV have been identified by Olech et al (120), who also revealed different levels of promoter activity for strains representing different subtypes. Therefore, differences between subtypes may be responsible for different transcriptional activity and replication rates, which may result in biological differences between SRLV subtypes.…”
Section: Tropism and Pathologymentioning
confidence: 99%